PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA KONSEP METABOLISME DENGAN MODEL CICR DI MAN 1 ACEH TIMUR - ZULFAWANI ZULFAWANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Biology learning, especially on the concept of metabolism, has not provided maximum learning outcomes (viewed from the students' learning completeness). It takes effort and improvement of the learning process for the better. The purpose of this study was to see the increase in student learning outcomes after participating in learning on the metabolic concept of students in class XII IPA-1 MAN 1 Aceh Timur in the academic year 2021/2022 for four face-to-face meetings. This research is a classroom action research so it requires research subjects totaling 26 students. The research was carried out in two cycles, namely cycle 1 and cycle 2. The research procedure went through four stages, namely planning, implementation, observation, and reflection. Test methods and observation of student learning activities are used to see the improvement of student learning outcomes. The results showed that the learning outcomes of students increased, this could be seen from the students' learning mastery both individually and classically. Data analysis in the first cycle, the average student learning outcomes were 70.68, as many as 36.24% of students completed, while in the second cycle increased to 81.91 as many as 75.63% of students completed learning. The average value of student learning activities in the first cycle is 65.47%, while in the second cycle there is an increase in student learning activities of 86.77%. Based on the results of data analysis in cycle 1 and cycle 2, it can be concluded that through CIRC learning can improve learning outcomes and student learning activities. So the conclusion is that learning biology on metabolic materials at Madrasah Aliyah Negeri 1 Aceh Timur applies the CIRC learning model to improve student learning outcomes and learning activities. ABSTRAKPembelajaran biologi khususnya pada konsep metabolisme belum memberikan hasil pembelajaran yang maksimal (dilihat dari ketuntasan belajar peserta didik). Diperlukan usaha dan perbaikan proses pembelajaran menjadi lebih baik. Tujuan penelitian ini untuk melihat peningkatan hasil belajar peserta didik setelah mengikuti pembelajaran pada konsep metabolisme peserta didik kelas XII IPA-1 MAN 1 Aceh Timur tahun pelajaran 2021/2022 selama empat pertemuan tatap muka. Penelitian ini merupakan penelitian tindakan kelas sehingga memerlukan subjek penelitian yang berjumlah 26 peserta didik. Penelitian dilaksanakan dua siklus yaitu siklus 1 dan siklus 2. Prosedur peneltitiannya melalui empat tahapan yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Metode tes dan observasi aktifitas belajar peserta didik digunakan untuk melihat peningkatan hasil belajar peserta didik. Hasil penelitian menunjukkan bahwa hasil belajar peserta didik meningkat, hal ini terlihat dari ketuntasan belajar peserta didik baik secara individu maupun klasikal. Analisis data pada siklus I, rata-rata hasil belajar peserta didik 70.68, sebanyak 36.24% peserta didik tuntas, sementara pada siklus II meningkat menjadi 81.91 sebanyak 75.63% peserta didik tuntas belajar. Nilai rata-rata aktifitas belajar peserta didik pada siklus pertama yaitu 65.47%, sedangkan pada siklus kedua terjadi peningkatan aktifitas belajar peserta didik sebesar 86.77%. Berdasarkan hasil anilisis data pada siklus 1 dan siklus 2 dapat disimpulkkan bahwa melalui pembelajaran CIRC dapat meningkatkan hasil belajar dan aktifitas belajar peserta didik. Sehingga simpulannnya, yaitu pembelajaran biologi pada materi metabolisme di Madrasah Aliyah Negeri 1 Aceh Timur menerapkan model pembelajaran CIRC meningkatkan hasil belajar dan aktifitas belajar peserta didik.